Prevalence of gastro-intestinal helminths in cattle at north Kashmir - ASHRAF, AIMAN; SHAHARDAR, R A; WANI, Z A; ALLAIE, I M (The Indian Journal of Animal Sciences, 2017)
Copro samples (1,126) of locally reared cattle at north Kashmir (Baramulla, Kupwara and Bandipora) were examined over a period of 1 year by qualitative and quantitative techniques. The overall prevalence of gastrointestinal (GI) helminths was 59.86% with trematodes, cestodes and nematodes in 11.63, 4.44 and 53.02% animals, respectively. Paramphistomes (7.10%) were the most prevalent trematodes followed by Fasciola spp. (4.53%) and Dicrocoelium spp. (0.27%). Prevalence of Moniezia spp. the only cestode found in the study was 4.44%. Among nematodes, the prevalence of strongyle worms was the highest (49.91%) followed by Trichuris spp. (3.64%) and Strongyloides spp. (2.04%). Seasonal variation revealed significantly highest prevalence of GI helminths during spring (68.21%) followed by autumn (67.50%), summer (55.59%) and winter (48.21%). Overall young cattle had significantly higher prevalence (68.13%) than adult animals (55.10%) but trematode infection was significantly higher in adults. Overall GI helminths were non-significantly higher in females (60.56%) as compared to males (58.24%) but the prevalence of paramphistomes was significantly higher in females. The prevalence of Dicrocoelium spp. and all the nematodes was nonsignificantly higher in males. EPG was ranging between 0 and 400 with an average EPG of 177.44±6.29. Highest EPG was recorded in spring (231.11±14.15) followed by summer (211.11±11.56), autumn (148.00±11.15) and winter (132.73±8.32). On coprocultural examination, Haemonchus spp. (65%) was found to be the most predominant strongyle worm followed by Bunostomum spp. (20%) and Trichostrongylus spp. (15%).